PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA MTs MUSLIM CENDEKIA - iran sairan (Jurnal Math-UMB.EDU, 2020)
In the context of mathematics learning, Problem Based Learning (PBL) is a mathematics learning strategy in the classroom with problem solving activities and provides more opportunities for students to think critically, creatively, reason, and communicate mathematically with their peers.Â  The focus of this study was the ability to solve math problems. Based on the preliminary research the students experienced errors in re-checking the synchronization of resolution with the given problem. This research was quasi experiment research. Naturally selected subjects have been formed in one intact group (naturally formed intact group). Based on the research data obtained can be described in the problem solving ability of students whose learning applies PBL learning models higher than the problem solving abilities of students with conventional learning, where the average value of the posttest in the experimental class is 71.03. This study conclude that PBL learning models give positive effect on problem solving skills on the subject of the Linear Equation System of Two Variables in class VIII MTs Muslim Cendekia Bengkulu Keywords:problem based learning, problem solving